Antimicrobial sonodynamic and photodynamic therapies against Candida albicans - Alves, Fernanda [UNESP]; Pavarina, Ana Cláudia [UNESP]; Mima, Ewerton Garcia de Oliveira [UNESP]; McHale, Anthony P.; Callan, John Francis (Taylor & Francis, 2018)
Candida albicans biofilms exhibit unique characteristics and are highly resistant to antifungal agents. Antimicrobial photodynamic therapy (aPDT) is an alternative treatment limited to treating superficial infections due to the poor light penetration. In this manuscript, the antifungal properties of sonodynamic therapy (SDT) were assessed. SDT uses ultrasound instead of light, enabling the treatment of deeper infections. Planktonic cells and biofilms of C. albicans were treated with aPDT or SDT, in addition to combined aPDT/SDT, with cell survival determined using colony forming units. The total biomass and structural integrity of the biofilms were also investigated. The results demonstrated that while individual aPDT or SDT eradicated suspensions, they had little impact on biofilms. However, combined aPDT/SDT significantly reduced the viability and total biomass of biofilms. Microscopic images revealed that biofilms treated with aPDT/SDT were thinner and comprised mainly of dead cells. These results highlight the potential of combined aPDT/SDT for the inactivation of C. albicans biofilms.
Keywords: anti-fungal; antimicrobial; biofilms; Candida albicans; photodynamic therapy; sonodynamic therapy